Design of adaptive threshold control algorithm based on real‐time CPU operation patterns for mobile devices. Issue 12 (1st June 2019) - Cho, H.H.; Eun, C.M.; Jeong, O.H.
Abstract : Thermal problems in conventional mobile devices are primarily managed by using software‐based techniques due to compact sizes and limited power budgets. Since these software‐based techniques incur inevitable performance degradation to reduce temperature, efficient thermal management techniques are essential for modern mobile devices. In this letter, the authors propose a novel control algorithm, which adaptively controls the threshold based on the power efficiency of mobile CPUs in real‐time. The authors validate the thermal mitigation capability and system performance of their proposed scheme using a commercial smartphone. The evaluation results indicate that the proposed scheme reduces the CPU and PCB temperature by 1.20 and 1.38%, respectively, and simultaneously improves overall system performance by 5.44%.